1970
DOI: 10.3329/imcj.v3i2.4219
|View full text |Cite
|
Sign up to set email alerts
|

Awareness on HIV/AIDS among the Blood Donors of a City Hospital

Abstract: This descriptive cross-sectional study was carried out on ‘HIV/AIDS awareness' among the blood donors of Dhaka Medical College Hospital. The aim of the study was to assess the level of awareness among blood donors on HIV/AIDS and to assess their knowledge regarding its prevention and control. A total of 110 (87.3% male, 12.7% female) donors participated in this study. Their mean age was 24.9 ± 5.2 years. More than 60% of the respondents had primary or secondary level of education. Two-thirds (66.11%) of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Level of awareness rose significantly with years of schooling. This finding is consistent with previous studies (Rahman & Rahman, 2007 ; Sultana, 2009 ; Yaya et al., 2016 ). Access to mass media also played important role in determining the state of subject’s awareness about HIV/AIDS.…”
Section: Discussionsupporting
confidence: 94%
“…Level of awareness rose significantly with years of schooling. This finding is consistent with previous studies (Rahman & Rahman, 2007 ; Sultana, 2009 ; Yaya et al., 2016 ). Access to mass media also played important role in determining the state of subject’s awareness about HIV/AIDS.…”
Section: Discussionsupporting
confidence: 94%
“…The findings of this study demonstrated that the one-third (32.89%) husbands are illiterate of them 50.29% have heard about HIV/AIDS and most of the husbands (67.11%) are literate of them almost all (79.52%) have heard about HIV and AIDS. It is a positive sign because Sultana [14] found that education plays an important role in preventing HIV/AIDS. Husband's occupation is an important predictor which helps his wife understanding through discussion about various topics especially STDs.…”
Section: Background Characteristics Of the Respondentsmentioning
confidence: 99%
“…Useful and fruitful media campaigns are strongly suggested for creating knowledge and awareness to be controlled the spread of HIV and AIDS [13]. Mass awareness campaigns on HIV/AIDS could improve the critical situation [14]. The STDs are increasing the likelihood of HIV transmission as well as having other reproductive health consequences of ever married women.…”
Section: Introductionmentioning
confidence: 99%